PROVIDING MAINTENANCE SERVICES TO NUCLEAR POWER PLANTS: THE ROLE OF SAFETY CULTURE - Androjna, Andrej; Račič, Zoran (Journal of Energy Technology, 2024)
After explaining basic terms and the relationships between the organizational and safety cultures, this paper illustrates the characteristics of the safety culture in the nuclear industry and, more specifically, in the maintenance of nuclear power plants (NPP). It further discusses the role of safety culture in organizations of external maintenance providers. The results clearly show that the standards and criteria of the safety culture applicable to plant employees are equally valid for external service providers. For the latter, assuring the highest levels of safety culture is a challenge, especially for those who do not provide services solely to the nuclear industry. The case on a leading Slovenian nuclear services provider, NUMIP d.o.o., illustrates its methods and activities for the continual improvement of safety culture in the organization.